Age and Gender Differences in the Well-Being of Midlife and Aging Parents with Children with Mental Health or Developmental Problems: Report of a National Study - HA, JUNG-HWA (2008)
Using data from the Study of Midlife in the United States (MIDUS), this article examines: (1) the effect of having children with developmental or mental health problems on parents’mental and physical health, (2) the extent to which this effect varies by parental age and gender, and (3) the effects of disability-related factors on the well-being of parents of children with disabilities. Compared to parents of non-disabled children, parents of disabled children experienced significantly higher levels of negative affect, marginally poorer psychological well-being, and significantly more somatic symptoms, controlling for sociodemographic variables. Mothers did not differ from fathers in their well-being. Older parents were significantly less likely to experience the negative effect of having a disabled child than younger parents, suggesting an age-related attenuation of the stress of non-normative parenting.